A STUDY OF RACISM, HOMOSEXUALITY AND SLAVERY APPLYING JUDITH BUTLER’S CONTAGIOUS WORDS IN PAKISTAN - Tamsila Naeem (International Conference on Social and Islamic Studies, 2021)
This qualitative study intends to examine racism, homosexuality and slavery as contagious wordsin Pakistan by applying Judith Butler’s notions presented in Excitable Speech in 1997.“Contagious words” is the expression, which talks about social taboos, immoral words, harmfulwords, etc. Nearly all types of contagious words and acts are considered illegal and unacceptablein any society in the world. These contagious words refer to racism, homosexuality, same-sexmarriage, child marriage, and forced marriage, slavery, bonded slavery, child labor, and the listgoes on. The applied theoretical model depends on Judith Butler’s notions introduced in her mostrenowned book Excitable Speech (1997). Judith Butler claims that despite the fact thesecontagious words and acts are controlled by the law and these practices are condemned bysocieties, the practices are covertly going on. The findings related to the objective of the studyreveals that the contagious speech acts are controlled by the powerful agencies in order to showtheir power. The results of the study show that the powerful agencies who are controlling thesecontagious acts and practices, are inherently inclined towards these contagious acts in most ofthe cases.